Assistance to Children Exposed to Domestic Violance: Situation in Lithuania - Indrašienė, Valdonė; Merfeldaitė, Odeta; Sadauskas, Justinas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of the study is to assess the organisation of assistance for children after domestic violence experience in Lithuania. The methods of scientific literature, analysis of strategic document and legal acts, synthesis and generalisation were used. The main findings:Children in Lithuanian mostly experience physical aggression, but in recent year’s case of psychological violence are becoming more and more frequent. Increase of psychological violence against children allows to believe that specialists of Child‘s Rights Protection divisions as well as other specialists more actively and successfully identify the children that experience psychological violence and manifestations of such violence and apply corresponding measures. The legal framework for prevention of violence against the child is and the child‘s health care has been created. In cases of violence against children support to the victim and his/her family is provided and coordinated systematically by specialists of various fields and institutions, according to the needs of the victim. The complex support required by the children after experienced violence and their families (psychological, social, legal and psychiatric) is basically provided by non-governmental organizations the most of which are located in the major cities. In more remote places for the suffered children and their families it is really confusing to get support, especially the lasting one